Prevalence and antibiotic resistance of Escherichia coli in urban and peri-urban garden ecosystems in Bangladesh - Pritom Kumar Pramanik; M. Nazmul Hoque; Md. Liton Rana; Md. Saiful Islam; Md. Ashek Ullah; Fahim Haque Neloy; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; Md. Tanvir Rahman (PLoS ONE, 2025)
In the past decade, there has been a notable rise in foodborne outbreaks, prominently featuring Escherichia coli as a primary pathogen. This bacterium, known for its prevalence in foodborne illnesses and as a reservoir of antimicrobial resistance, was isolated from raw vegetables, soil, and water samples collected from rooftop and surface gardens in urban (Dhaka North City Corporation; DNCC and Dhaka South City Corporation; DSCC) and peri-urban (Gazipur City Corporation; GCC) areas of Bangladesh. In this study, 145 samples including vegetables (n = 88), water (n = 27) and soils (n = 30) from DNCC (n = 85), DSCC (n = 30), and GCC (n = 30) were analyzed to assess the prevalence of E. coli using culture, biochemical tests, and PCR targeting the malB gene. E. coli was detected in 85 samples, indicating an overall prevalence of 58.62% (95% CI: 50.48–66.31). In urban areas (DNCC and DSCC), the prevalence rates were 44.70% and 80.0%, respectively, with surface gardens showing higher contamination rates (70.83%) than rooftop gardens (46.57%). In the peri-urban GCC, overall prevalence of E. coli was 76.7%, with rooftop gardens more contaminated (93.33%) than surface gardens (60.0%). Antibiogram profiling of 54 randomly selected isolates revealed 100% resistance to ampicillin, with varying resistance to ciprofloxacin (25.92%), tetracycline (14.81%), cotrimoxazole (14.81%), imipenem (9.25%), and fosfomycin (1.0%). Notably, all isolates were susceptible to ceftazidime, gentamicin, chloramphenicol, nitrofurantoin, and cefotaxime. Multidrug resistance (MDR) was found in 14.81% of isolates. The blaTEM gene was present in 81.48% of the isolates, while the tetA gene was detected in 3.70%. These findings underscore the urgent global health concern posed by the significant presence of E. coli in fresh vegetables, highlighting the need for improved safety measures and monitoring to prevent the spread of antimicrobial resistance through the food chain.